2007
DOI: 10.1080/00016340701644843
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcome of fetal cystic hygroma diagnosed in the first trimester

Abstract: These data suggest that the prognosis of fetal cystic hygroma detected during the first trimester is poor, and show that sonographic evaluation of fetal nuchal translucency thickness in the first trimester is crucial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 27 publications
3
41
1
2
Order By: Relevance
“…It was reported that chromosomal abnormalities were present in 55% (22 of 40) in the cystic hygroma group, with 9 of 22 (40.9%) of Turner syndrome cases [16] . The aneuploidy rate in our cystic hygroma patients (72.2%) was higher than those in other studies, and ranged from 51 to 61% [17][18][19][20] . In addition to Turner syndrome, cystic hygroma is reported to be associated with other aneuploidies such as trisomy 21, 13 and 18 [21] .…”
Section: Discussioncontrasting
confidence: 47%
“…It was reported that chromosomal abnormalities were present in 55% (22 of 40) in the cystic hygroma group, with 9 of 22 (40.9%) of Turner syndrome cases [16] . The aneuploidy rate in our cystic hygroma patients (72.2%) was higher than those in other studies, and ranged from 51 to 61% [17][18][19][20] . In addition to Turner syndrome, cystic hygroma is reported to be associated with other aneuploidies such as trisomy 21, 13 and 18 [21] .…”
Section: Discussioncontrasting
confidence: 47%
“…Jaques S. et al dans une étude menée à Virginia hospital, portant sur les hygromas kystiques congénitaux cervical observent qu'il n'y avait pas de survivants néonatals dans le groupe avec caryotype anormal et que deux à trois pourcent de nouveau-nés étaient normaux lorsque le diagnostic de l'hygroma kystique était fait in utéro [7]. Graesslin et al, constatent que le sex-ratio apparaissait en défaveur des foetus de sexe féminin et l'issue était défavorable (fausse couche, interruption volontaire, des anomalies structurelles graves) dans 77,7% des cas (56/72) [8].…”
Section: Discussionunclassified
“…The presence of increased nuchal translucency thickness in chromosomally normal fetuses has been found in association with cardiac and cerebellar anomalies in isolation, and also in fetuses later identified with a variety of genetic syndromes [7][8][9][10][11] . The cause of the increased nuchal translucency in any of the above-mentioned situations is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have looked at the pregnancy outcome in chromosomally normal fetuses with increased first-trimester nuchal translucency and found fetuses with a variety of structural anomalies and genetic syndromes [7][8][9][10][11] . To our knowledge, first-trimester ultrasound has not been previously reported as useful in the prenatal diagnosis of RSS.…”
Section: Introductionmentioning
confidence: 99%